PENGUATAN DEMOKRASI LOKAL DI ERA DIGITAL: STUDI KASUS PERAN ORGANISASI SOSIAL PADA PILKADA ENREKANG 2024 - Nuha, Uli; Haerusman, Haerusman; Amaliah, Ema; Alrif, Syaharuddin; Mulyadi, Andi; Lukman, Adli; Herwin, Herwin (Jurnal Daya Saing, 2026)
The use of digital technology in the modern era provides significant opportunities for strengthening local democracy, including in the context of Regional Head Elections. This study aims to analyze the role of social organizations in strengthening local democracy in Enrekang Regency in the 2024 Pilkada. This study uses a qualitative approach with a case study design, involving 10 key informants consisting of representatives of social organizations, community leaders, and digital media managers who are active in the Pilkada process. Data were collected through in-depth interviews, participant observation, and document analysis. The results of the study indicate that social organizations are able to increase public political awareness, expand access to information through digital media, and facilitate inclusive political discussions. However, challenges such as the digital divide and the spread of misinformation are significant obstacles in this process. This study concludes that collaboration between local governments, social organizations, and the community is crucial to maximize the potential of digital technology in creating inclusive, transparent, and sustainable political participation. The findings of this study provide a practical contribution to strengthening technology-based democracy at the local level and offer a novelty in a collaborative model for strengthening digital-based local democracy